The Critical Analyses of Propaganda of the Terrorism Deed - Masuku, Mfundo Mandla; Mlambo, Victor H.; Ngwenya, Bhekani J. (Technium Social Sciences Journal, 2021)
This paper analyses the propaganda of the terrorism deed as the form of terrorism that is different from mainstream terrorism. The propaganda by the deed is underpinned by specific political action which is meant to serve as a catalyst for revolution and terrors groups have over the decades used the propaganda by the deed to expand their operations and seek sympathizers. The concept became consolidated in the late 19th and early 20th in Europe when proponents were driven by violence which included bombings and assassinations, targeted at the ruling class. The aim was to entrench the spirit of revolt, to consolidate the observation that the state was not omnipotent and by offering hope to the downtrodden, and also to expand support for anarchist movements as the state grew more repressive in its response. This paper argues that modern-day terrorism has greatly made use of the propaganda by the deed to carry out its violent missions. Therefore, this paper examines the use of propaganda by the deed by modern-day terror groups, it reflects on how terrorism has evolved not only to be linked to non-state actors but also observes how states have become sponsors of terrorism to advance their interests, finally, the paper how examines how terrorism has emerged to become a global security concern in a globalized era.